2005
DOI: 10.1021/pr0502121
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Characterization of the Cytoskeleton of NK-Like Cells

Abstract: The cytoskeleton is a dynamic structure that contributes to cell function in terms of shape, movement, transport and secretion. It also provides a platform for regional activities such as signaling, biosynthesis and energy production. The present manuscript describes a method for cytoskeleton isolation based on capture with magnetic microbeads and its application to the analysis of the NK like cell line, YTS. The isolated proteins were separated by SDS-PAGE and the peptides from the in gel digested proteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Our previous proteomic analysis of YTS cells identified PPP1R9B as a component of their cytoskeleton [16]. As PPP1R9B has been shown to regulate actin deposition and neurite formation, we questioned whether PPP1R9B might also be involved in immunological synapse formation [19].…”
Section: Ppp1r9b Accumulates At the Nkis And Sites Of Homotypic Cell mentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous proteomic analysis of YTS cells identified PPP1R9B as a component of their cytoskeleton [16]. As PPP1R9B has been shown to regulate actin deposition and neurite formation, we questioned whether PPP1R9B might also be involved in immunological synapse formation [19].…”
Section: Ppp1r9b Accumulates At the Nkis And Sites Of Homotypic Cell mentioning
confidence: 97%
“…In a previous study, we identified a number of cytoskeletal components of the NK-cell line, YTS [16]. Potential candidates of NKIS proteins were selected for analysis based on their predicted or known roles in cell polarization in other cell types.…”
Section: Introductionmentioning
confidence: 99%
“…IQGAP has been detected in NK cells [24] and YTS cells [12]. However, it is unclear as to what roles it plays in cell-mediated effector processes.…”
Section: Effects Of Iqgap1 Silencing On Yts Cellsmentioning
confidence: 99%
“…41: 2763-2773 DOI 10.1002 Molecular immunology 2763 determined, in part because of the difficulties associated with the isolation of these structures. In an effort to define the NKIS composition, we previously performed a proteomic analysis of the cytoskeletal elements of an NK-like cell line YTS, with subsequent structural and bioinformatic approaches to identify candidate synapse components [12]. IQGAP1was identified as one of the cytoskeletal components of the YTS cells [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation